Status Keberlanjutan Agribisnis Aren di Kabupaten Garut: Pendahuluan, Metode penelitian, Hasil dan pembahasan, Kesimpulan, Ucapan terima kasih, Daftar pustaka - Yuslam Fauzan, Muhammad Irfan; Awaliyah, Fitri (Universitas Garut, 2024)
Sustainability of sugar palm agribusiness is a strategic topic in Garut Regency because of its significant role in supporting the local economy and maintaining environmental balance. This research aims to evaluate the sustainability status of sugar palm agribusiness through analysis of ecological, economic and social aspects. The research method uses a quantitative approach with descriptive statistical analysis based on primary and secondary data. The research respondents consisted of 30 sugar palm farmers who were selected using purposive sampling based on certain criteria. The research results show that the ecological aspect has a good level of sustainability, supported by the use of organic fertilizer, low use of pesticides, and optimal soil absorption capacity. The economic aspect is also at a fairly good level of sustainability because sugar palm makes a significant contribution to farmers' income, even though there are obstacles in access to capital and marketing. On the other hand, social aspects still require more attention due to weak farmer participation in management, minimal institutional support, and lack of information regarding agribusiness sustainability. Overall, sugar palm agribusiness in Garut Regency has the potential for positive sustainability, but to achieve this strategic steps are needed such as strengthening institutions to assist farmers, increasing market access so that sugar palm products are more competitive, developing sustainable technological innovation, and encouraging active involvement of farmers in agribusiness management. It is hoped that this integrated step can support the sustainability of sugar palm agribusiness in a comprehensive, optimal, holistic and sustainable manner.